MENINGKATKAN KESADARAN MASYARAKAT UNTUK MEMATUHI PROTOKOL KESEHATAN DI ERA PPKM DENGAN MEDIA POSTER MELALUI WAGRAM (WHATSAPP, INSTAGRAM DAN YOUTUBE) - Mutia Evi Kristhy; Arif Lukman Hakim; Erwin Widyawan; Cindy Claudia; Martha Renatha Limbong; Wismiati Sarvon; Arianto Kapitan Laut; Disa; Astuti Telaumbanua; Ahmad Fadilah Akbar; Gomgom Aldian; Jhosua Kristian Maranatha; Sri Wahyuni; Mariani; Wantoni Mahendra; Lianata (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
The world is surprised by the presence of new virus called Corona virus new type (SARS-CoV-2) whic its illness is called Corona virus Disease (Covid-19) in the beginning of 2020. To prevent the spread of Covid-19, the government has conducted various prevention efforts. Starting from the prevailing of area quarantine, PSBB (Big Scale of Social Restriction), PPKM (Implementation of Rectrictions on Community Activities), and so on. As a form of community service, the authors in community service activity (KKN) conducted one of work program related to PPKM. The writing of this paper focuses on the effort to increase the community awareness to obey health protocol in PPKM era with poster media through whatsapp group, instagram, and youtube. The method used was descriptive method. The issuance of this PPKM policy aims to control the community activity which has potential to enlarge the transmission of Covid-19. It it is not done, sooner or later it will impact on various sectors either social, culture, or economic growth will experience difficulty, industry will not run as it should be, or the community will lost their livelihood. As a result, by the presence of this socialization by using poster media through whatsapp group and instagram the community can stay productive by considering health protocol during Covid-19 pandemic. Therefore, the community must start to adapt with new life habit during PPKM